Profiled M-advertising Framework for Consumer Advertising - Gangabada, G.L.P.N.; Premaratne, S. C. (Department of Computer Science Faculty of Applied Sciences University of Sri Jayewardenepura, 2013)
Mobile advertising and profiled advertising has become major discussion topics recently. With rapid development of mobile technology in the last decade, many e-business organizations are trying to combine the latest mobile technologies with customer profiling in order to increase the reachability of their product information among the target market. This paper presents a potential mechanism to enhance such mobile advertising by improving existing user profile methods. The main goal of this research is to introduce a novel user profiling mechanism that can be used to improve the productivity of a mobile advertising system. The proposed system is capable of providing additional information such as video, audio, etc. about advertisements to the user while giving profile-based and proximity suggestions.
Keywords: Profiled m-marketing, collaborative filtering, user profiling